Analisis kesulitan belajar Siswa dalam pembelajaran tatap muka terbatas pada masa pandemi covid-19 - Windi Erlina; Wawan Shokib Rondhi; Himmatul Ulya (IKIP Siliwangi, 2023)
This study aims to analyze students' learning difficulties in limited face-to-face learning during the COVID-19 pandemic in Grogolan Village, to be precise, students of SD Grogolan 01, Dukuhseti District, Pati Regency. This research began with problems in the era of the COVID-19 pandemic. Limited face-to-face learning is an alternative so that learning continues even though the COVID-19 pandemic is still hitting. One of the influencing factors in limited face-to-face learning activities is the role of parents in assisting children to study at home. The research method used is qualitative with a phenomenological approach. This research was conducted in Grogolan Village and focused on the fifth grade students of SD Grogolan 01, which consisted of 3 students. Data collection techniques in this study using observation, interviews and documentation. This study uses the validity of the data by triangulation. There are 3 stages of data analysis in this study, namely data reduction, data presentation, and conclusions. The results showed that students' learning difficulties during the implementation of PTM were limited to various, including students who had not mastered the material presented by the teacher to the maximum, difficulties in solving story problems in mathematics lessons and questions whose answers were not in the book, and lack of student interest in PTM. limited.